Núcleo Interdisciplinar de Educação em Direitos Humanos: pela construção da cultura da paz no Corpo de Bombeiros Militar do Tocantins - Guimarães, Halyny Mendes (Universidade Federal do Tocantins, 2017)
Society, at a global level, is experiencing crises and conflicts that demand a formation of a culture of peace and tolerance. Added to this, a climate of insecurity and discredit in relation to public institutions and their agents prevails in Brazil. In this context, Public Security has great relevance in the consolidation of the culture of respect for human rights and protection of citizens' legal assets. After all, the promotion of justice is not exclusive to the Judiciary. Promoting justice is the responsibility of all Powers and requires the involvement of all society. And the Military Fire Brigade, a public safety organ of high social recognition, plays an important role as a human rights educator, through its agents. In order to do so, it is necessary for society to recognize the effectiveness of these rights in relation to Public Security agents, as well as for them to move towards the theme, believing that human rights are for the protection of all people, regardless of any nature; And also to respect these rights, including with respect to each other, in the fire station environment. This dissertation will analyze the role of military firefighters as trainers in human rights education, examining the feasibility and challenges of developing these rights in militarized environments. The study aims at the perception of the human rights of the Tocantins military firefighters, which was extracted through an unidentified questionnaire applied to the military. Its objective is to demonstrate the need for a broad human rights education within the Corporation. The method used is the dialectic, in which man is admitted as a historical-social subject, who, at the same time as he produces society, is produced by him. The theoretical categories of contradiction, wholeness and mediation will be explored in particular. As a result, it was found that firefighters, potential human rights educators, do not have sufficient intimacy with the subject, nor do they often understand themselves as subjects of such rights. In view of this, it is proposed the creation of the Interdisciplinary Center for Human Rights Education within the scope of the Military Fire Brigade of Tocantins, with the involvement of other organs, teachers, researchers and civil society. It will be an instrument that can influence the relations of power and in the action, inside and outside the Corporation, tracing strategies for the improvement of human rights education. The development of respect for human rights and the consolidation of a culture of peace in the Fire Department will certainly bring important consequences for the community, thus contributing to the good of society in general.